A new prognostic index of severity of intellectual disabilities in Cornelia de Lange syndrome. Issue 2 (5th May 2016) - Cereda, Anna; Mariani, Milena; Rebora, Paola; Sajeva, Anna; Ajmone, Paola Francesca; Gervasini, Cristina; Russo, Silvia; Kullmann, Gaia; Valsecchi, Grazia; Selicorni, Angelo
Abstract : Cornelia de Lange syndrome is a well‐known multiple congenital anomalies/intellectual disability syndrome with genetic heterogeneity and wide clinical variability, regarding the severity of both the intellectual disabilities and the physical features, not completely explained by the genotype‐phenotype correlations known to date. The aim of the study was the identification of prognostic features, ascertainable precociously in the patient's life, of a better intellectual outcome and the development of a new prognostic index of severity of intellectual disability in CdLS patients. In 66 italian CdLS patients aged 8 years or more, we evaluated the association of the degree of intellectual disability with various clinical parameters ascertainable before 6 months of life and with the molecular data by the application of cumulative regression logistic model. Based on these results and on the previously known genotype‐phenotype correlations, we selected seven parameters to be used in a multivariate cumulative regression logistic model to develop a prognostic index of severity of intellectual disability. The probability of a mild ID increases with the reducing final score less than two, the probability of a severe ID increases with the increasing final score more than three. This prognostic index allows to define, precociously in the life of a baby, the probability of a better or worse intellectual outcome in CdLS patients. © 2016 Wiley Periodicals, Inc.